ESTIMATION OF KARANJIN IN BARK AND SEED EXTRACT OF PONGAMIA PINNATA PLANT AND MARKETED KARANJIN OIL USING THIN-LAYER CHROMATOGRAPHY DENSITOMETRY - ASHWINI SHIVAJI SHENDAGE; NAVNEET KHURANA; GURVINDER SINGH; RAJESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The present study focuses on the development and validation of a high-performance thin-layer chromatography (HPTLC) method for the quantification of karanjin in ethanolic extracts of bark and seeds of Pongamia pinnata, as well as in marketed karanjin oil. P. pinnata, a member of the Fabaceae family, is recognized for its traditional medicinal properties, primarily attributed to karanjin, a furanoflavonoid with notable biological activities. Methods: The HPTLC method was optimized using a silica gel stationary phase and a mobile phase comprising toluene and ethyl acetate in a ratio of 8:2. Parameters such as specificity, linearity, limit of detection (LOD), and limit of quantification (LOQ) were assessed according to ICH Q2 (R1) guidelines. Results: Karanjin showed good linearity over the range of 100–500 ng/band with a correlation coefficient (r2>0.99). The LOD and LOQ were 3.15 ng/band and 9.56 ng/band, respectively. Precision studies demonstrated % relative standard deviation values <1% for both intra-day and inter-day analysis. The method showed high accuracy with recovery values ranging from 99.0% to 101.2%. Assay results indicated karanjin content of 3.05±0.02% w/w in bark extract, 30.55±0.30% w/w in seed extract, and 33.40±0.19% w/w in marketed oil. Conclusion: The developed HPTLC method offers a rapid, sensitive, and reliable analytical approach for the estimation of karanjin, thereby facilitating its application in both pharmaceutical and agricultural contexts.